2016
DOI: 10.3390/su8070652
|View full text |Cite
|
Sign up to set email alerts
|

Performance Indicator Framework for Evaluation of Sustainable Tourism in the Taiwan Coastal Zone

Abstract: Abstract:Surrounded by the ocean, Taiwan has been increasingly developing coastal tourism projects. Concerns that negative impacts might be brought about by prosperous tourism have resulted in a recent focus on sustainable tourism. Sustainable tourism involves policies that acknowledge the interdependences among the environment, the community, and the economy. The goal of sustainable tourism is to enhance and protect the environment while satisfying basic human requirements, as well as those of the contemporar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
5

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(24 citation statements)
references
References 35 publications
0
17
0
5
Order By: Relevance
“…It is also similar to sample sizes in regional studies of this sort (for example, 12 and 15 experts in two phases [55], 25 interviewees [36]). The sample was expanded using the "snowball" sampling system.…”
Section: The Samplementioning
confidence: 63%
“…It is also similar to sample sizes in regional studies of this sort (for example, 12 and 15 experts in two phases [55], 25 interviewees [36]). The sample was expanded using the "snowball" sampling system.…”
Section: The Samplementioning
confidence: 63%
“…Here, the effective approach to establishing the preliminary indicator framework is to analyze the existing literature and the laws and regulations of food safety regulatory [58]. On this basis, the quality risk evaluation indicator system for the food supply chain can be built by the method which is based on the fuzzy analytic hierarchy process (FAHP) proposed by Wang et al [59], shown as Table 1. According to Table 1, the evaluation objects for quality risk of the food supply chain can be generalized into five categories: raw material supply risk [33][34][35][36][37]; production and processing risk [34,[37][38][39][40][41][42]; logistics, warehousing, and transportation risk [40][41][42][43][44][45][46]; sales and consumption risk [42,[47][48][49][50][51]; and government regulatory risk [52][53][54][55][56][57].…”
Section: Quality Risk Evaluationmentioning
confidence: 99%
“…Wang et al, noting an increasing trend in Taiwan for coastal tourism projects, also made use of the FDM and fuzzy analytic hierarchy process (FAHP) methods to build a performance-indicator framework for identifying the key factors affecting the sustainable development of such tourism. Following a similar general approach to those of the studies cited above, the present research will establish performance indicators for the operations management of eco-museums, using FDM for the expert screening of potential indicators, and ANPM for exploring such indicators' interactive influences [20]. Their profiles are provided in Table 1.…”
Section: Research Processmentioning
confidence: 99%